The impact of El Niño-southern oscillation to the wind and solar data in Malaysia. Issue 1 (March 2020) - Albani, A.; Ibrahim, M.Z.; Ghani, S.; Zulkifli, M.R.; Ganesan, N.N.A.G.
Abstract: Malaysia has initiated initiatives to use renewable energy as a resource of electricity generation since 2011 through the establishment of laws and policies related to renewable energy. The geographical location of Malaysia has led to limited of intermittent renewable energy resources and requires a more detailed study of the various factors impacting electricity generation. This paper aims to understand the impact of El Niño-Southern Oscillation (ENSO) events on the reanalysis wind and solar data. The Wavelet Transform will be used to study the relationship between the reanalysis wind and solar dataset with the Multivariate ENSO index in the Malaysia region. During Very Strong and Strong El Nino, the site experienced an increment of both wind velocity and solar irradiance and reduced during La-Nina. This ENSO impact study is essential as a reference for future wind and solar energy development planning, energy predicting, and risk valuation in Malaysia.